The Stressful Life of the Urban Consumers: The Case of Dhaka City Residents - Masoom, Muhammad Rehan (Frontiers in Psychology, 2021)
The present research examines the metropolitan mental life of consumers of Dhaka, which is one of the most densely populated and least livable cities in the world. Though mental life encompasses a range of factors, the study considered the dynamic interplays of the most pertinent ones, such as perceived stress, the sense of control, materialistic values, and religiosity. These variables were measured and quantified by commonly used measurement tools; a recursive structural equation model was constructed to unearth the causal connections among those variables. By using a 57-item questionnaire, the study surveyed 1068 shoppers living in 10 different zones of the city. The estimated covariance by the multivariate structural equation model indicates that perceived stress is significantly associated with the sense of control; while religiosity and materialistic value-orientation were negatively associated, there are no significant relationships between religiosity and sense of control, and materialism and sense of control; Perceived stress and Religiosity are found to be positively associated. The estimated independent sample t-tests show that while no significant difference is found in sense of control by gender, females are more religious, less materialistic but perceive their lives as more stressful than the males. The findings may help to interpret both the cognitive and affective responses of the consumers of urban residents.